Pemanfaatan Kecerdasan Buatan dalam Teknologi Multimedia Pembelajaran: Peluang, Tantangan, dan Implikasi Pedagogis - Syah, Suri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This study comprehensively examines the use of artificial intelligence (AI) in multimedia learning technology, highlighting its opportunities, challenges, and pedagogical implications. By analyzing the latest literature, this article discusses how AI revolutionizes learning personalization, enhances interaction, and optimizes the evaluation process through various multimedia applications (Rahman & Sari, 2022). The methodology used is a systematic literature review, synthesizing findings from various relevant studies to identify trends, case studies, and research gaps (Santoso, 2022). The results of the study indicate that AI significantly improves the effectiveness and efficiency of learning, but also poses serious challenges related to the gap in technology access, ethical issues such as data privacy and algorithmic bias, and the potential for student dependency (Wibowo, 2022). This article concludes that the implementation of AI in multimedia learning requires a balanced approach, emphasizing human-AI collaboration, developing digital literacy of teachers and students, and a strong policy framework to ensure ethical and inclusive use (Prabowo, 2023).